7
$\begingroup$

The first step in calculating the variance of a Binomial Random Variable is calculating the second moment.

enter image description here

I have no idea as to how the last two steps have happened. Why is a n(n-1)p^2 outside the first summation and a similar expression outside the second? Also, how did the expression turn out to be the last equation?

$\endgroup$

3 Answers 3

4
$\begingroup$

First term is obtained as follows:

\begin{align} \sum_{j=0}^{n} \frac{n!(j^2-j)}{(n-j)!j!}p^j(1-p)^{n-j} &= \sum_{j=2}^{n} \frac{n!(j^2-j)}{(n-j)!j!}p^j(1-p)^{n-j}\tag{1}\\&=\sum_{j=2}^{n} \frac{n!(j(j-1))}{(n-j)!j!}p^j(1-p)^{n-j} \tag{2}\\ &= \sum_{j=2}^{n} \frac{n!}{(n-j)!(j-2)!}p^j(1-p)^{n-j} \tag{3} \\ &= n(n-1)\sum_{j=2}^{n} \frac{(n-2)!}{(n-j)!(j-2)!}p^j(1-p)^{n-j} \tag{4}\\ &= n(n-1)p^2\sum_{j=2}^{n} \frac{(n-2)!}{(n-j)!(j-2)!}p^{j-2}(1-p)^{n-j} \tag{5} \\ &= n(n-1)p^2\sum_{j'=0}^{n-2} \frac{(n-2)!}{(n-2-j')!(j')!}p^{j'}(1-p)^{n-2-j'} \tag{6} \\ &= n(n-1)p^2 \tag{7} \\ \end{align}

where equation $(1)$ is due to $j^2-j=0$ if $j=0$ or $j=1$, hence we can start summing from $2$ rather than $0$.

Equation $(2)$ is just $j^2-j=j(j-1)$.

Equation $(3)$ is due to $j!=(j-2)!j(j-1)$

Equation $(4)$ is due to $n!=(n-2)!n(n-1)$.

Equation $(5)$ is just factorize $p^2$ outside.

Equation $(6)$ is a change of variable of $j'=j-2$

To obtain equation $(7)$, notice that in equation $(6)$, the term inside the sum if the pmf of binomial distribution with parameter $n-2$ and $p$.

I will leave the second term as an exercise.

$\endgroup$
2
$\begingroup$

They distributed out constant factors from series so that a change of variables would make it the series of probabilities for a binomial expansion $(p+1-p)^{n-1}$.   They did not show their work, thinking it would be obvious.   Clearly it is not.

I'll just do one of the terms $${ \quad \sum_{j=0}^n\dfrac{n!\ j}{(n-j)!\ j!}p^j(1-p)^{n-j} \\ = \sum_{j=0}^n \dfrac{n(n-1)!\,j}{(n-1-j+1)!\, j\, (j-1)!} p\, p^{j-1}(1-p)^{n-1-j+1} \\ = np \sum_{j=0}^n\dfrac{(n-1)!}{(n-1-(j-1))!\,(j-1)!}p^{j-1}(1-p)^{n-1-(j-1)} \\ = np \sum_{j-1=-1}^{n-1}\binom{n-1}{j-1}p^{j-1}(1-p)^{n-1-(j-1)} \\ = np \sum_{j-1=0}^{n-1}\binom{n-1}{j-1}p^{j-1}(1-p)^{n-1-(j-1)} \\ = np \sum_{k=0}^{n-1}\binom{n-1}k p^k(1-p)^{n-1-k} \\ = np (p+(1-p))^{n-1} \\ = np }$$

The other term follows likewise. Of particular note we use the conveniention that $\binom{r}{-1}=0$.

$\endgroup$
1
$\begingroup$

The $n$ and $n-1$ are coming out of the $n!$ remember that $n!=n*(n-1)*(n-2)!$. The $p^2$ came from the $p^j$ since $p^j=p^{j-2}*p^2$. Once this terms are out both sums (separately) are equal to the probability mass function of a binomial random variable hence they sum to 1. Hence the result.

$\endgroup$
2
  • $\begingroup$ In that case, why have the numbers on the summations changed? $\endgroup$
    – SDG
    Oct 18, 2017 at 3:27
  • $\begingroup$ For the first sum when $j=0$ or $1$ the term is 0 since $j^2-j=0$, for the second sum when $j=0$ the term is 0. So you don't have to consider those. $\endgroup$ Oct 18, 2017 at 3:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.